2021
DOI: 10.15537/smj.42.3.20200768
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic pain on sleep quality and depression

Abstract: Objectives: To examined the impacts of chronic pain on depression and poor sleep quality dimensions as well as the mediating function of poor sleep quality in the pathway between chronic pain and depression. Methods: Between March 2019 and February 2020, we conducted a cross-sectional study on 233 chronic pain patients in 2 tertiary hospitals in Riyadh, Saudi Arabia. Results: Of the 233 patients, 36% had depression, while 66.1% had poor sleep quality. Chronic pain intensity and pain disability significantly ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…Supporting these findings, current reports showed that SARS-CoV-2 infection is associated with a high prevalence of anxiety and depression afterwards (17)(18)(19). Persistent and disabling symptoms could induce depressive symptoms and anxiety (20)(21)(22) and persistent physical symptoms after COVID-19, including gastrointestinal and respiratory symptoms, are significantly associated with a higher probability of developing psychiatric symptoms (19,23,24). Reciprocally, however, patients presenting with depression and anxiety also tend to have more somatic and pain complaints (25).…”
Section: Introductionmentioning
confidence: 81%
“…Supporting these findings, current reports showed that SARS-CoV-2 infection is associated with a high prevalence of anxiety and depression afterwards (17)(18)(19). Persistent and disabling symptoms could induce depressive symptoms and anxiety (20)(21)(22) and persistent physical symptoms after COVID-19, including gastrointestinal and respiratory symptoms, are significantly associated with a higher probability of developing psychiatric symptoms (19,23,24). Reciprocally, however, patients presenting with depression and anxiety also tend to have more somatic and pain complaints (25).…”
Section: Introductionmentioning
confidence: 81%
“…Likewise, between 2019 and 2020, Alhalal et al carried out a cross-sectional study in Saudi Arabia on 233 chronic pain patients to examine the impact of chronic pain on depression [ 19 ]. They used the Chronic Pain Grade Scale to evaluate pain and the Center for Epidemiologic Studies-Depression scale to assess the patients' depressive symptoms.…”
Section: Reviewmentioning
confidence: 99%
“…If these private data are not properly protected, it will lead to the leakage of the user's private data. Therefore, data collection privacy protection schemes for medical service systems are becoming more and more important [ 14 , 15 ].…”
Section: Smart Medical Care Interventionmentioning
confidence: 99%